Cover Image: The fungivorous amoeba Protostelium aurantium targets redox homeostasis and cell wall integrity during intracellular killing of Candida parapsilosis (Cellular Microbiology 11/2021). (14th October 2021) - Radosa, Silvia; Sprague, Jakob L.; Lau, Siu‐Hin; Tóth, Renáta; Linde, Jörg; Krüger, Thomas; Sprenger, Marcel; Kasper, Lydia; Westermann, Martin; Kniemeyer, Olaf; Hube, Bernhard; Brakhage, Axel A.; et al.
Abstract : The fungivorous amoeba Protostelium aurantium feeds on a wide range of fungal species. The image shows amoebae digesting GFP‐expressing cells of the human pathogenic yeast Candida parapsilosis . For further details, readers are referred to the article by Radosa et al. on p. e13389 of this issue.